Phalsa is a profitable fruit crop in Jammu subtropics - Kumar, Rakesh; Kumar, Vijay; Singh, V B; Trilokia, Meenakshi; Bakshi, Parshant (Indian Horticulture, 2019)
Phalsa (Grewia subinaequalis L.) is presently cultivated as a minor fruit crop and its cultivation is gaining popularity in rainfed area of Jammu subtropics. This fruit crop has great potential in production and its nutraceutical values due to higher antioxidant content present in it. It can be grown as an intercrop in newly as well as already established orchards due to its small stature. Its fruit can be processed into ready-to-serve beverage. Thus, it will also play an important role in diversification.